PENGEMBANGAN PROTOTIPE SISTEM PENDETEKSI KEBOCORAN GAS DENGAN MEKANISME MONITORING DAN PERINGATAN DINI ADAPTIF SECARA REAL-TIME - Mudhiah Fadhilah Rahmah; Naurah Zalfa Aqiila; M. Pasha Hadi Pratama; Muhammad Dzaki Fauzan; Ratna Atika (Teknik Elektro Polsri, 2026)
The use of Liquefied Petroleum Gas (LPG) as a household fuel continues to increase due to its practicality and efficiency. However, the use of LPG also poses a risk of gas leakage, which may lead to fires or explosions if not detected at an early stage. This study aims to design and develop a gas leakage detection system prototype based on Arduino Uno using an MQ-2 sensor in a miniature kitchen environment. The research employed a prototype development method, including hardware design, system programming, and device testing. The prototype was designed as a miniature room measuring 40 cm × 35 cm × 27 cm and equipped with an MQ-2 sensor, a 16×2 LCD, LEDs, a buzzer, servo motors, and a DC fan. The test results showed that the MQ-2 sensor was capable of detecting gas leakage effectively based on changes in sensor readings. At sensor values of 0–99, the system remained in a safe condition, indicated by the green LED being active while all actuators remained inactive. Meanwhile, at sensor values of 100–400, the system detected gas leakage and automatically activated the red LED, buzzer, DC fan, and servo motors to open the room ventilation. The LCD also successfully displayed real-time system status information. Based on the testing results, the developed prototype was able to detect gas leakage and provide automatic responses as an initial mitigation effort to improve household safety. Keywords: LPG Gas Leakage, MQ-2 Sensor, Arduino Uno, Gas Detection System, Household Safety